Percepções de maturidade em gerenciamento de projetos à luz da nova gestão pública: uma investigação com gestores das secretarias estaduais do Rio Grande do Norte - Nascimento, Thiago Cavalcante (2011)
This study aimed to measure the perception of maturity project management of state boards of Rio Grande do Norte by the perception of its managers. Argues that project management has been highlighted as a critical factor for the success of any organization, because the projects are directly related to the set of activities that result in organizational innovation as products, services and processes and the improvement of project management is directly aligned with the main pillars of the New Public Management. Methodologically, this is a quantitative research of a descriptive nature in which 161 forms were applied with coordinators and subcoordinators of state departments of Rio Grande do Norte, culminating in a sampling error of less than 6% to 95% confidence according to the procedures finite sampling. The process of tabulation and analysis was done using the package Statistical Package for Social Sciences - SPSS 18.0 and worked with techniques such as mean, standard deviation, frequency distributions, cluster analysis and factor analysis. The results indicate that the levels of maturity in project management in state departments of Rio Grande do Norte is below the national average and that behavioral skills are the main problem for improving management in these departments. It was possible to detect the existence of two groups of different perceptions about the management of projects, indicating, according to the managers, there are islands of excellence in project management in some sectors of the state departments. It was also observed that there are eight factors that affect maturity in project management: Planning and Control , Development of Management Skills , Project Management Environment , Acceptance of the Subject Project Management , Stimulus to Performance , Project Evaluation and Learning , Project Management Office and Visibility of Project Managers . It concludes that the project management in state departments of Rio Grande do Norte has no satisfactory levels of maturity in project management, affecting the levels of efficiency and effectiveness of the state apparatus, which shows that some of the assumptions that guide the New Public Management are not getting the levels of excellence nailed by this management model